Comparative Analysis of Durability and Cost Efficiency Between Hot Rolled Sheet (HRS) and Cold Paving Hot Mix Asbuton (CPHMA) in Road Maintenance - Alif Iqbal Nur Hidayat; Hera Widyastuti (Institut Teknologi Sepuluh Nopember (ITS), 2026)
Natural asphalt deposits on Buton Island are estimated to reach 677 million tons, but their utilization remains suboptimal. Additional challenges, such as the increasing number of vehicles and issues related to Over Dimension Over Load (ODOL) on commercial vehicles, contribute to widespread road damage and shortened pavement lifespans. One potential solution for efficient road maintenance is the use of Cold Paving Hot Mix Asbuton (CPHMA), a flexible pavement mixture that is heated during mixing but can be laid at ambient temperatures, thus promoting the utilization of Buton asphalt. This study compares HRS (Hot Rolled Sheet) and CPHMA wich used in routine road maintenance in Malang Raya with laboratory tests and cost analyses.. The HRS materials were sourced from PT. Piranti Utomo Makmur, while the CPHMA materials were provided by PT. Ketahanan Aspal Nasional. Testing confirmed that both the aggregate and asphalt materials meet technical specifications. Marshall test results for CPHMA after a 1x30-minute immersion showed a strength of 576.3 kg, while a 1x24-hour immersion produced a strength of 508.4 kg, resulting in a residual strength index of 88.22%. For HRS, the 1x30-minute immersion yielded a strength of 1,091.2 kg, and the 1x24-hour immersion produced 986.3 kg, with a residual strength index of 90.39%. These results indicate that HRS exhibits better durability compared to CPHMA. From a cost perspective, however, CPHMA proves more economical, with a cost of IDR 245,500.00/m2 compared to HRS at IDR 248,800.00/m2. The difference of IDR 3,300.00/m2 makes CPHMA a more cost-effective option and could be a quicker option for routine road maintenance